RETRACTED: The impact of quarantine pests on forest health in Krasnoyarsk krai - Popova Valentina; Fedonova Polina; Sultson Svetlana; Kulakova Nadezhda; Mikhailov Pavel; Khizhniak Natalia (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001